Monitoring System at CTV : Sarajevo - Arcel, Libby Tata (Array, 2003)
The main frame of the monitoring system at Centre for torture victims is described. During the first two years of work at CTV Sarajevo (1997 - 1999) the monitoring program consisted of several questionnaires which were administrated to each client in the following order. First, the person who received the client , (in most cases the General practitioner(G.P.) during his/hers first visit to the Centre filled the Identification paper with basic data about the client (name, age, sex and the reasons for coming).The client was given his own code number and code number of his/hers family. Then, according to the clients need, G.P. gave recommendation for the client to see different other team professionals. If the client accepted and needed the referral , thereafter all other documentation could be filled out. This was done by psychologists and consisted of Questionnaire on socio- demographic data, List of traumatic events, which represents the adaptation of the list published by Mollica et al. (1992) which listed all major traumatic events client was exposed to. As measure of coping with stress and traumatic events the Scale of Ways of Coping with Stress was used (Folkman, Lazarus, 1988) adapted by Arcel and Ljubotina (Arcel et al., 1998). Questionnaire SCL 90-R (Derogatis, 1977) was used as a measure of general psychopathological symptoms, while the Mississippi PTSD Scale (Keane, Caddell & Taylor, 1988) was used for measurement of Posttraumatic Stress Disorder. Screening of the degree of general health problems was done by G.P. who filled out the BO list of somatic problems (Zerssen, 1971). At the beginning of the psychiatric treatment the psychiatrist had to fill the Algorithm on Torture (Bø ; ; jholm, Foldspang, Juhler, Kastrup, Skylv, Somnier, 1992) in order to document the maltreatment and torture methods client was exposed to.